Diplomasi Pariwisata Indonesia Dalam Meningkatkan Wisatawan Australia ke Indonesia Pada Pandemi COVID-19 Tahun 2020-2022 - Fayza Maritza Putri Agustono (2023)
This study aims to discuss Indonesian tourism diplomacy in Australia in order to increase Australian tourists to Indonesia during the 2020-2022 COVID-19 pandemic by using the theory of diplomacy and the concept of tourism diplomacy. The method used is descriptive qualitative using primary data sources and secondary data. Data collection techniques using literature review and interviews. Researchers used data analysis techniques in this study using qualitative data analysis according to Miles and Huberman (1984), namely, activities that include data reduction (data reduction), data display (presentation of data), and conclusion drawing or verification (conclusion/verification). The final results of this research show that during the COVID-19 pandemic, namely from 2020 - 2022, Indonesia continues to carry out a number of diplomacy, especially diplomacy in the tourism sector to increase Australian tourist visits to Indonesia. Indonesia's diplomacy has been quite successful in increasing the number of Australian tourists to Indonesia, however, it has not yet reached the tourist target like before the pandemic. However, diplomacy to increase the number of tourists from 2020 to 2022 is experiencing a better improvement.